Comparative Analysis of Intestine Microbiota of Four Wild Waterbird Species - Laviad-Shitrit, Sivan; Izhaki, Ido; Lalzar, Maya; Halpern, Malka (Frontiers in Microbiology, 2019)
Waterbirds are ubiquitous and globally distributed. Yet, studies on wild waterbirds' gut microbiota are still rare. Our aim was to explore and compare the gut microbial community composition of wild waterbird species. Four wild waterbird species that are either wintering or all-year residents in Israel were studied: great cormorants, little egrets, black-crowned night herons and black-headed gulls. For each bird, three intestinal sections were sampled; anterior, middle and posterior. No significant differences were found among the microbiota compositions in the three intestine sections of each individual bird. Each waterbird species had a unique microbial composition. The gut microbiota of the black-headed gulls’ fundamentally deviated from that of the other bird species, probably due to a very high abundance (58.8%) of the genus Catellicoccus (Firmicutes). Our results suggest a correlation between the waterbird species’ phylogeny and their intestine microbial community hierarchical tree, which evinced phylosymbiosis. This recent coinage stands for eco-evolutionary patterns between the host phylogeny and its microbiota composition. We conclude that eco-evolutionary processes termed phylosymbiosis may occur between wild waterbird species and their gut microbial community composition.